The Sporozoite's Journey Through the Mosquito: A Critical Examination of Host and Parasite Factors Required for Salivary Gland Invasion - Kojin, Bianca B.; Adelman, Zach N. (Frontiers in Ecology and Evolution, 2019)
Although much progress has been made in the fight against malaria, the number of people that contract this disease due to the bite of an Anopheline mosquito remains unacceptably high. A better understanding of the relationship between the Plasmodium parasite and its vector is of extreme importance and may allow for the development of new tools to fight the disease. In particular, new genome editing techniques may allow the modification or removal of factors critical for parasite traversal of the vector mosquito. In this review, we aim to highlight what is known about important molecules encoded by the mosquito or parasite involved in this close interaction, focused on a specific window of the parasite life cycle inside the mosquito: from egress and release of the sporozoites from the oocyst into the hemolymph, until salivary gland penetration. While sophisticated molecular tools have already helped to understand aspects of parasite-mosquito interactions, our understanding of this brief period is still limited. Here, we discuss the evidence surrounding essential parasite and mosquito factors relating to sporozoite invasion of the salivary glands, and emphasize the areas where the lack of information is limiting the advance of strategies to manipulate the mosquito in order to block the transmission of malaria parasites.